Regional Distribution of German-Czech Multinationals on the Domestic Market - Michael Moritz; Johannes Schaeffler (European Regional Science Association (ERSA), 2012)
This article deals with the domestic location of German multinational firms which have affiliates in the Czech Republic. Due to the common border the Czech Republic represents an attractive target country for both vertical and horizontal direct investments. In the year 2009 the sum of direct and indirect German investments in the Czech Republic added up to 22 bn exteuro. This amount is far higher than the investments in other Central and Eastern European Countries (CEEC) and also in Japan or in one of the BRIC countries Brazil, Russia, India and China. On the one hand, the still existing wage gap offers the opportunity to offshore activities abroad by reason of cost advantages. On the other hand, the increasing purchasing power of Czech customers provides favorable chances to acquire a new market. Corresponding to the main motive for a company to invest in the Czech Republic, there are differences in the relevance of possible determinants for the decision to go abroad, e.g. the distance between the German capital provider and the Czech affiliate. On the basis of a register of firms made available by the German-Czech Chamber of Industry and Commerce we present findings on the growing economic integration between the two countries. Almost 80% of the headquarters of German investors are located in the four federal states Bavaria, Baden-Wuerttemberg, Hesse and North Rhine-Westphalia. The eastern German New Laender are far less engaged in investments in the neighboring country. We use count data models in order to account for the distribution of the dependent variable, i.e. the number of investors in the German domestic regions. Controlling for several economic factors it can be concluded that the headquarters of German multinationals investing in the Czech Republic are preferably located in areas with high regional GDP. The distance to the common border plays an important role for the decision to enter the Czech market. In addition, regions that are situated directly at the German-Czech border are involved at an above-average rate in foreign direct investments. Thereby, location patterns differ between manufacturing firms and both trading and service companies. The findings illustrate the relevance and different impact of regional aspects for foreign direct investments dependent on the target sector in the country of destination.
Keywords: 330